Helminth diversity in Pimelodus blochii Valenciennes, 1840 (Osteichthyes: Pimelodidae) in two Amazon Rivers - Cavalcante, Pedro Hercílio de Oliveira (Parasitol Res, 2020)
Structure of the helminth community and analyses of helminth population parameters of Pimelodus blochii collected in the Xapuri River in comparison with those in the Acre River were evaluated. Eight adult helminth species were found parasitizing P. blochii in the Acre River: the nematodes Orientatractis moraveci, Rondonia rondoni, Philometroides acreanensis, Cucullanus (Cucculanus) pinai pinai, Procamallanus (Spirocamallanus) pimelodus, Rhadochona acuminata, and Brasilnema sp., and the trematode Dadaytrema oxycephala. For Xapuri’s fishes, nine helminth species were found: the nematodes O. moraveci, R. rondoni, C. (C.) pinai pinai, Procamallanus (Spirocamallanus) rarus, P. (S.) pimelodus, R. acuminata, Brasilnema sp., and Cystidicolidae gen. sp., and the trematode D. oxycephala. Nematode and Acanthocephala larvae were also reported. Helminth abundance, prevalence, and diversity were influenced by seasonality and locality (river). The helminth parasites from Acre’s fishes formed a subset of the helminth community of the Xapuri’s. The results indicate an influence of the environmental characteristics of the rivers on the helminth community structure and diversity. This is the first study of the parasite community of P. blochii in the Xapuri River. The paretheses of (Spirocamallanus) and (S.) should not be in italics all along the text and tables.